The impact of Business Innovation Affecting the Peformance of Business Service Secter in Luang Prabang - VONGMANICHANH, Nouy; CHANTHAVONE, Thongphanh; OUTHACHACK , Sindavone; THIPDACHANH, Soulichanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
To study on The impact of business innovation affecting the peformance of Business service secter in Luang Prabang, which is a quantitative analysis and have research objective: 1)The level of business innovation factors of the service business Entrepreneurs, 2) The level of performance of the service business Entrepreneurs and 3) The impact of Business innovation affecting The peformance of business service secter in Luang Prabang by questioning and surveyed 225 people. The data was analyzed by the Pearson Product Moment Correlation Ceofficient and Stepwise Multiple Regression Analysis. The study found that most entrepreneurs are small service business operators by period of doing business 5-10 years, with average income per month between 10.000.000-30.000.000 Kip,. The registered capital is between 51,000,000-100,000,000 kip, and the Working capital coming from increase in the capital of the business owner. Business innovation of Entrepreneurs were that the holistic approach in the high criteria and descending by means are information, personnel, process, planing and leadership. Furthermore, the aspects about the performance are of business service are in the great level and descending by means are customer, learning and development, internal process and finance. The impact of business innovation affecting the peformance of business service secter in Luang Prabang consist of four factors such as: 1) personnel innovation, 2) process innovation, 3) information innovation, 4) planing innovation had statistical significance at the level of 0.1.